A Meta-Analysis on the Immunogenicity of Homologous versus Heterologous Immunization Regimens against SARS-CoV-2 Beta, Delta, and Omicron BA.1 VoCs in Healthy Adults - Ndzouboukou, Jo-Lewis Banga; Kamara, Abdul A.; Ullah, Nadeem; Lei, Qing; Fan, Xiong-lin (Journal of microbiology and biotechnology, 2025)
Since the outbreak of the COVID-19 pandemic, SARS-CoV-2 has not stopped evolving, leading to the emergence of variants of concern (VoCs) involved in significant immune escape. Here, we compared the immunogenicity of different prime-boost vaccination regimens against SARS-CoV-2 wildtype (WT) and its Beta, Delta, and Omicron BA.1 VoCs. We used 5 databases to retrieve publications and random-effect models to estimate pooled neutralization titers. We included 11 randomized controlled trials (RCTs) and 16 non-RCTs, 10 prime-boost vaccination regimens, and 4598 subjects. We found neutralization activity against SARS-CoV-2 decreased with virus evolution. The heterologous immunization was more effective. The increase in neutralization titers against SARS-CoV-2 WT and Beta, Delta, and Omicron BA.1 VoCs after heterologous immunization was 1.41(95%CI:0.82-2.01), 0.90(95%CI:0.39-1.41), 1.23 (95%CI: 0.81-1.65), and 1.32 (95%CI: 0.99-1.65), respectively. Furthermore, the booster dose of viral vector vaccine did not show a higher increase in neutralization titers against SARS-CoV-2 WT(MD=0.48; 95%CI:-1.12-1.09), Beta (MD=0.20; 95%CI:-0.26-0.67), Delta (MD=0.35; 95%CI:-0.09-0.79), and Omicron BA.1 (MD=0.38; 95%CI:-0.14-0.89) VoCs. The combination of inactivated-recombinant protein vaccines showed a higher increase in neutralization titers (Beta: MD=1.88 and Delta: MD=1.70) than other combinations of vaccines. However, only a combination of mRNA-viral vector vaccines showed a higher increase in neutralization titers (MD:1.52; 95%CI:0.34-2.70) against Omicron BA.1 VoC. Interestingly, the viral vector-mRNA immunization regimen appears better compared to mRNA-viral vector regimen, especially against Beta and Delta VoCs. Overall, the type of combination followed by the order of administration of COVID-19 vaccines could be a potential vaccine strategy against the occurrence of SARS-CoV-2 variants.